The preoperative value of fine‐needle aspiration in adult soft tissue lesions: An analysis of 514 cases at Shanghai Cancer Center - Meng Fang; Bingnan Wang; Biqiang Zheng; Wangjun Yan (Cancer Medicine)
Abstract Background Fine‐needle aspiration (FNA) cytology is a rapid, inexpensive, and uncomplicated method. However, its role in the assessment of soft tissue lesions (STL) remains controversial, and its ability to guide surgical treatment remains unclear. This study investigated the positive predictive value (PPV) of FNA for detecting malignancy and its guiding role in the surgical treatment of STL. Methods We retrospectively reviewed 514 patients with STL who underwent preoperative FNA and surgical resection between March 2015 and August 2021. Imaging assessments confirmed that radical surgery was possible. The FNA results were compared with the final postoperative histopathology. Results Of the 514 patients with STL, 496 (mean age, 48.9 years; range, 21–91 years) were eligible for analysis, the male to female ratio was 111:100. According to the 496 FNA results, 90 (18.2%) were positive for malignancy, 84 (16.9%) were suspicious for malignancy, 80 (16.1%) were spindle cell present, and 242 (48.8%) were negative for malignant cells. Compared with postoperative histopathology, FNA correctly detected all 90 malignant lesions and 203 of the 242 benign lesions. A total of 39 false‐negative results were obtained. FNA showed an accuracy of 88.3%, sensitivity of 69.8%, specificity of 100%, negative predictive value (NPV) of 83.9%, and PPV of 100%. In the other seven validation cohorts (n = 1157), FNA had a consistently high PPV, with values all more than 93%. Conclusion Our results demonstrate that FNA has a high PPV for detecting malignancy. For patients with resectable lesions and malignant FNA, the core needle biopsy (CNB) step can be omitted with multidisciplinary evaluation, and subsequent radical surgery can be performed.